2005
DOI: 10.1002/neu.20174
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to intermittent hypoxia enhances mice performance in water maze and 8-arm radial maze tasks

Abstract: Hypoxia has generally been reported to impair learning and memory. Here we established a hypoxia-enhanced model. Intermittent hypoxia (IH) was simulated at 2 km (16.0% O2) or 5 km (10.8% O2) in a hypobaric chamber for 4 h/day from birth to 1, 2, 3, or 4 week(s), respectively. Spatial learning and memory ability was tested in the Morris water maze (MWM) task at ages of postnatal day 36 (P36)-P40 and P85-89, respectively, and in the 8-arm maze task at P60-68. The long-term potentiation (LTP), synaptic density, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…Compared with the control group, the spatial cognitive ability of mice exposed to hypoxia once was not changed. Zhang et al [24,32] have reported that intermittent hypoxia could enhance spatial cognitive ability in young mice but did not affect this ability in adult mice. Others also reported that brief hypobaric hypoxia enhanced animals' cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the control group, the spatial cognitive ability of mice exposed to hypoxia once was not changed. Zhang et al [24,32] have reported that intermittent hypoxia could enhance spatial cognitive ability in young mice but did not affect this ability in adult mice. Others also reported that brief hypobaric hypoxia enhanced animals' cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The ICR mice were developed from the Swiss-Webster albino mice and have been used as a model to explore the cognitive ability under hypoxia condition [24] . A total of 90 male adult ICR mice (16.0-22.0 g) were separated into 3 groups randomly and exposed, respectively, to hypoxia for 4 runs (group H4), 1 run (group H1) and 0 runs (group H0).…”
Section: Animal Modelmentioning
confidence: 99%
“…For example, chronic intermittent hypoxia in neonatal mice (exposure to 16% O 2 for 4 h/day ! 3 weeks) significantly improved longterm spatial learning and memory tested in water maze and radial arm paradigms [24] . In contrast, exposure of immature rats to 10% O 2 (6 h/day for 20 days) resulted in significant long-term alteration of spatial memory tested using water maze [11] .…”
Section: Discussionmentioning
confidence: 99%
“…This group has significant experience with the administration of systemic IH, and has conducted extensive studies on the role of IH in respiratory plasticity [3][4][5][6][7] . This work, and the recent finding that chronic IH increased neurogenesis in the rodent CNS [8][9][10] , forms the basis for the exploration of acute in vivo hypoxia as a preconditioning stimulus (i.e., prior to tissue harvest) on the subsequent culture of neural stem/progenitor cells (NPCs) 11 . Remarkably, when mouse pups were exposed to a brief (<1 hr) period of acute intermittent hypoxia (AIH), cells that were harvested from the subventricular zone (SVZ) had significantly increased capacity for expansion as neurospheres or adherent monolayer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In other published work, neonates were treated as a litter with the dam in hypobaric chambers, which allows for chronic dosing, less handling prior to treatment, and maintained maternal contact during treatment 9 . The current approach bypasses repeated treatments to a breeding female, or the use of a different dam for each experiment.…”
Section: Introductionmentioning
confidence: 99%